2013
DOI: 10.2214/ajr.12.10011
|View full text |Cite
|
Sign up to set email alerts
|

JOURNAL CLUB: How Radiation Exposure Histories Influence Physician Imaging Decisions: A Multicenter Radiologist Survey Study

Abstract: Purpose To evaluate the influence of patient-level radiation exposure histories on radiologists’ imaging decisions. Materials and Methods We conducted an IRB exempt, HIPAA compliant, physician survey study in three academic medical centers. Radiologists were asked to make a prospective imaging recommendation for a hypothetical patient with a history of multiple CT scans. We queried radiologists’ decision-making, evaluating whether they: incorporated cancer risks from previous imaging; reported acceptance (or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…While it is an important step to improve clinicians’ awareness of the risks of radiation exposure from advanced medical imaging, a more nuanced approach or the provision of information about the relevant clinical impact may be more useful to inform clinical decisions. The cancer risk associated with cumulative radiation exposure from multiple imaging tests is not well understood by the radiology and medical community 37 38. Whether cumulative radiation exposure information would be clinically relevant warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…While it is an important step to improve clinicians’ awareness of the risks of radiation exposure from advanced medical imaging, a more nuanced approach or the provision of information about the relevant clinical impact may be more useful to inform clinical decisions. The cancer risk associated with cumulative radiation exposure from multiple imaging tests is not well understood by the radiology and medical community 37 38. Whether cumulative radiation exposure information would be clinically relevant warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used decision-analytic (Markov) modeling techniques to quanti-I n recent years, there have been increasing concerns about cancer risks associated with CT, particularly in clinical settings where patients are scanned multiple times [1][2][3][4][5][6][7][8][9][10][11][12]. CTguided renal mass ablation represents one such circumstance and is perceived to be associated with a high burden of radiation exposure [10,11].…”
mentioning
confidence: 99%
“…The inclusion of this information in the radiology department is primarily useful for population-based data gathering and not in the care of individual patients (Durand 2011). Another study reported, however, that at present, most radiologists incorporate risks from past exposures to guide prospective imaging decisions (Pandharipande et al 2013). From another perspective, offering the patient and health care professional information such as cumulative dose estimates compared to natural background radiation and associated LAR compared to natural risks can also decrease the probability that irrational radiation fears will prevent a medically necessary examination from taking place in the future (Durand and Mahesh 2012;Eisenberg et al 2012).…”
Section: Discussionmentioning
confidence: 99%